Biodegradable mushroom-based transparent paper - Syifa, Zainab; Wan Nawawi, Wan Mohd Fazli (Anirudh Dular, 2018)
There is growing interest towards biopolymerbased nanofibres due to its superior mechanical properties and environmentally friendly functions. Chitin nanofibres may be of interest as a component for nanocomposites. Decolourisation effectively enhance the desirability of chitin nanofibres as it can be used without changing the natural colour of base materials.Decolourised chitin nanofibres from waste Pleurotus ostreatus (oyster mushroom) is biocompatible, biodegradable and sustainable. It combat issues existing with the current commercial source of chitin, crustacean shells, which are more difficult to culture, limited to seasonal and geographical aspects and have inconsistent quality due to water pollution. In the present study, chitin nanofibre was extracted using hot water extraction and through a deproteinisation process using NaOH. Chitin thin film was prepared using a filtration method and decolourised using H2O2 at different concentrations. The mechanical properties of decolourised films were tested using a tensile machine. The results showed that the most optimum condition for chitin thin film was 60% H2O2 for 18 h at 40 °C with a tensile strength, modulus and toughness of 26 MPa, 10 GPa and 108 MJm-3 respectively. It was found that fungal-based chitin have a higher toughness than commercial crustacean-based chitin. Chitin nanofibres derived from mushrooms have a high potential in developing nanomaterials and biocomposites.